Poverty orderings and intra-household inequality: The Lost Axiom - Peluso, Eugenio; Trannoy, Alain (Journal of Income Distribution®, 2009)
We investigate under which conditions it is possible to infer theevolution of poverty at the individual level from the knowledge ofpoverty among households. Poverty measurement is approached bythe poverty orderings introduced by Foster and Shorrocks (1988). Theanalysis is based on a reduced form of household bargaining (Pelusoand Trannoy, 2007) and provides results in terms of preservation ofpoverty orderings. We point out the main analogies and differencesbetween inequality and poverty assessment, expressing them in termsof empirically testable conditions. In particular, knowing the changein poverty at the household level is not sufficient to deduce a similarchange in poverty at the individual level. We need to know the changein the household income distributions far beyond their poverty line.The focus axiom does not hold in this context.